The Expected Gender Roles on the Main Characters and Their Responses in Queen of Tears - Aurel Valensia Hartono (Institute of Research and Community Outreach - Petra Christian University, 2026)
Queen of Tears, 2024’s top k-drama, explores a unique couple dynamic: a conglomerate heiress marries a village man. This article examines the expected gender roles imposed on Baek Hyun Woo and Hong Hae In , and their responses. The findings indicate that modern society still expects Baek Hyun Woo to be the breadwinner and the head of the family, while Hong Hae In is expected to be a homemaker and submissive. Baek Hyun Woo shows conformity to the expectations as he internalizes his roles. However, Hong Hae In shows ambiguity, performing nonconformity yet also conforming to gender roles in situations where it benefits her. The study concludes that traditional gender roles expectation persists in modern Korean society. Individuals are able to respond through nonconformity and conformity, driven by internalized values and beneficial considerations.